2021
DOI: 10.3390/agronomy11030544
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ozonated Fertigation in Pepper Cultivation under Greenhouse Conditions

Abstract: Ozone has a high oxidizing power avoiding the presence of residues, so it is a good candidate for use in organic farming. However, its application in fertigation has been little studied. Two experiments were conducted simultaneously to check the aims of this work. The aim of the first experiment was to study pepper response under the nutrient solution supply and the application of O3 and its interactions, and the aim of the second experiment was to determine the optimal dosage of O3 to be supplied, from the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…Regarding N extraction, fertigation with the nutrient solution increased the total nitrogen uptake by the plant with a higher allocation of N in the stem to the detriment of the root and flowers. Similar findings were reported by Colunje et al [34] in pepper seedlings fertigated with nutrient solution, where there was a higher accumulation of N in the stems.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Regarding N extraction, fertigation with the nutrient solution increased the total nitrogen uptake by the plant with a higher allocation of N in the stem to the detriment of the root and flowers. Similar findings were reported by Colunje et al [34] in pepper seedlings fertigated with nutrient solution, where there was a higher accumulation of N in the stems.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, the supply of increasing ozone concentrations (from 0 to 2 mg L −1 ) to the nutrient solution increased pigments concentrations in tomato plants as reported by Tahamolkonan et al [33]. Nevertheless, the decline in leaf proline concentration under rising O 3 was consistent with the results obtained by Colunje et al [34] in pepper grown under similar experimental conditions.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Leaves showed the opposite behavior to roots because the plants treated with H 2 O 2 had a lower number of leaves and leaf area; nevertheless, García-Jiménez [60] found a higher stem DW in green bean and melon plants subjected to a chemical oxygenate application to the fertigation solution. Colunje et al [61] also found a similar behavior in pepper crops supplied with ozonated fertigation. For this reason, this effect could be related to oxygenated nutrient solution more than to a specific effect of H 2 O 2 .…”
Section: Plant Morphological and Physiological Parametersmentioning
confidence: 64%